Characterization and Bifidobacterium sp. growth stimulation of exopolysaccharide produced by Enterococcus faecalis EJRM152 isolated from human breast milk. (15th February 2019) - Kansandee, Wiratchanee; Moonmangmee, Duangtip; Moonmangmee, Somporn; Itsaranuwat, Pariyaporn
Highlights: Enterococcus faecalis EJRM152 produced the highest amount of exopolysaccharide (EPS). Two peaks of purified EJRM152 EPS consisted of glucose, galactose, rhamnose, arabinose and fructose. EJRM152 EPS showed functional groups including hydroxyl and carbonyl. EJRM152 EPS revealed good ability to stimulate the growth of Bifidobacterium sp. Abstract: Sixty lactic acid bacteria (LAB) isolated from human breast milk were screened for exopolysaccharides (EPS) production. EPS characterization and Bifidobacterium sp. growth support were investigated. The highest EPS-producing isolate was EJRM152 which identified as Enterococcus faecalis (98% similarity) based on the 16S rDNA gene sequence. Product yield coefficient (YEPS/x ) and EPS production were 3.68 and 4.32 g/l, respectively. Crude EPS was purified by DEAE-cellulose and a Sephacryl S-400 column, and it revealed different molecular weights and molar ratios of glucose, galactose, rhamnose, arabinose and fructose. FT-IR spectroscopy of EPS showed functional groups including hydroxyl and carbonyl. B. animalis TISTR 2194, B. breve TISTR 2130, B. bifidum TISTR 2129, and B. longum TISTR 2195 grew well in media containing EPS, comparing with commercial prebiotics. Results suggest that EPS produced by E. faecalis EJRM152 could be a potential candidate prebiotic.